INNOVATORY PRINCIPLES AND THEIR APPLICATION IN PRACTICE (Perner's Contacts, 2015)
The aim of this paper is to highlight the importance of continuous improvement of enterprise processes, which can be achieved by application of advanced and management practices. In the paper is given theoretical overview of selected methods, whose implementation can for the enterprise signify the significant positive changes leading to long-term prosperity.
Keywords: processes improvement, Kaizen, CRAFT method, costs